Wind turbine optimal control for reduction of structural loads in strong winds : : doctoral thesis - Petrović, Vlaho 1985 (V. Petrović ; Fakultet elektrotehnike i računarstva, 2013)
SUMMARY: In this thesis, control algorithms for reduction of wind turbine structural loads in strong winds have been researched. Such reduction is essential for prolongation of expected lifetime of wind turbine and for enabling further increase of its dimensions and rated power. Two approaches are considered for achieving reduction of wind turbine structural loads. Firstly, a control algorithm is designed for very high wind speeds (typically present during storms). This control algorithm enables wind turbine operation even when standard control system has to shut the wind turbine down thus improving wind farm behaviour in the electrical grid. An online optimisation for determining worst-case prediction of the wind speed is used, and based on such prediction, wind turbine power reference is changed to avoid excessive wind turbine structural loads. A second approach for reduction of wind turbine structural loads described in the thesis is focused on wind speeds above nominal wind speed. Standard individual pitch control algorithms and higher harmonic control algorithms are extended to enable the reduction of structural loads caused by rotor asymmetry. Furthermore, appropriate transformations of structural loads are defined that enable the use of structural load measurements from any part of the wind turbine, both rotating and non-rotating, to achieve reduction of structural loads. The reduction of structural loads is incorporated in a multi-criteria controller to improve wind turbine performance, with special emphasis on the satisfaction of pitch actuator constraints. To this end, a procedure is derived that allows better integration of the pitch actuator limitations (when considering structural loads reduction) within the model predictive control strategy. Finally, two scaled wind turbine models suitable for experimental validation of control algorithms in wind tunnels are presented. Such scaled models bridge the gap between numerical simulations and field tests, thus improving the procedure for validation of new control algorithms. Reported experimental results indicate that the presented scaled wind turbine models can be used for this purpose. -